Association between Microalbuminuria and MYH9 Gene Polymorphisms in Hypertensive Iraqi Patients with Metabolic Syndrome - Jasim, Alaa Fahem; Al-Tu'ma, Fadhil Jawad; Faisal, Dhafir Abdul-Mahdi (Journal of Contemporary Medical Sciences, 2021)
Objective The presented work aimed to study the correlation between microalbuminuria and MYH9 (T>C) (rs3752462) gene polymorphisms in metabolic syndrome of Iraqi patients. Methods This study was a cross-sectional study. Sample size was 140 persons of both gender selected randomly between April 1, 2019 and Aug. 15, 2020. They are divided into two groups, 80 with metabolic syndrome patients and 60 with control groups subdivided into another two groups: 30 persons with obese and 30 persons without obese. The distribution of sample according to the gender, the number of males had metabolic syndrome were 47 and female 33, but in obese healthy control the number of males were 19 and female 11, while in non-obese healthy control the number of males were 15 and female 15. The age groups were ranged between 40 and 60 years. Typing of MYH9 was performed by refractory mutation system-polymerase chain reaction (ARMS-PCR). The current study was performed to investigate the SNPs that affected MYH9 gene which was (T>C) (rs3752462). Results There was a significant difference between blood sugar, HbA1c, total cholesterol, TG, VLDL-C, LDL-C, blood urea, microalbuminuria, BMI, and HOMA-IR in metabolic syndrome patients as compared with healthy control groups (P ≤ 0.01). The significant result (P ≤ 0.01) were appeared between TT for MYH9 genotype patients and obese control with biochemical parameters (Blood glucose, HbA1c, TC, TG, VLDL-C, and LDL-C). The correlation between TT SNP for MYH9 genotype patients and non-obese control with biochemical parameters is significant result (P ≤ 0.01 and P ≤ 0.05) (Blood glucose, HbA1c, insulin, TC, TG, VLDL-C, LDL-C, urea, and microalbuminuria). The significant result (P ≤ 0.01 and P ≤ 0.05) appeared between CT for MYH9 genotype patients and obese control with biochemical parameters (Blood glucose, HbA1c, TC, TG, and VLDL-C) respectively. Conclusions There is a significant difference between blood glucose, HbA1c, total cholesterol, TG, VLDL-C, LDL-C, blood urea, microalbuminuria, BMI, and HOMA-IR in metabolic syndrome patients and healthy control groups (P ≤ 0.01). Also, a significant result (P ≤ 0.01) obtained between TT for MYH9 genotype patients and obese and non-obese control with some biochemical parameters. (P ≤ 0.01 and P ≤ 0.05). The significant results (P ≤ 0.01 and P ≤ 0.05) appear between CT for MYH9 genotype patients and obese control with some biochemical parameters.